Analisis Peningkatan Life skill Mahasiswa dalam Pembelajaran Metoda PJBL Pada Mata Kuliah Fisika Pada Prodi Teknik Elektro - Nuri, Nuri; Bijanto, Bijanto (UPEJ Unnes Physics Education Journal, 2021)
Student competencies need to be adjusted to the demands of the business and industrial world, the mental readiness of graduates to face the world of work and the needs of competence by industry that is increasingly fast. Weak afternoon graduates will face increasingly tough challenges. The writer's experience in previous research related to project learning is that life and career skills can increase student productivity. Life and career skills include competencies to be a flexible person, guide and lead others, manage time and goals, work independently, work effectively in a team. Implementing PJBL in physics subjects in the STTP electrical engineering study program is important to do as an effort to increase the competence and competitiveness of university graduates, as well as provide 21st century competence to face demographic challenges and life probabilities. This idea is stated in the Beginner Lecturer Proposal (PDP) with the title Analysis of Life and Career Skills Improvement for Electrical Engineering Students Through Methods, PJBL in Advanced Physics Subjects. The purpose of this research is to produce an appropriate PJBL implementation design in improving life and career skills for students, to analyze the values of life and career skills in students. The research method is Preexperimental Design. only involving the experimental class, without involving the control class. In general, PJBL learning can improve the five points of students' Life skill abilities with an average grade of 63.6 to 94.9 with an n-gain of 0.9 with high criteria